BURUNG-BURUNG YANG MEMANFAATKAN Spathodea campanulata dan Melastoma malabahtricum DI KAWASAN HUTAN KAMPUS UNIVERSITAS BANGKA BELITUNG - Lastri Dwi Saputri; Nur Annis Hidayati; Ani Mardiastuti (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2020)
Indonesia is known as the country with the second highest megabiodiversity after Brazil because of its rich flora and fauna. One proof of its natural wealth belongs to birds which reached 1,777 species. The existence of thousands of birds in several aspects of life that discusses finance, culture, science and research. Based on this, it is necessary to do research on birds that utilize Red Flower trees (Spatodhea campanulata) and Kedebik bushes (Melastoma malabraticum) in the forest area of ​​the Bangka Belitung University campus. The method used in this study is a calculation point that determines the observation point based on the Red Tree flower (Spatodhea campanulata) and the Kedebik bush (Melastoma malabraticum) in the forest area of ​​the Bangka Belitung University campus. The birds that use the Red Flower tree and the Kebebik bush found in the Bangka Belitung University campus forest are 5 orders grouped into 10 families and 17 species. The order with the largest number of families is Order Cuculiformes, which consists of 7 families.